Comparative proteomic analysis of three Lactobacillus plantarum strains under salt stress by iTRAQ. (14th January 2021) - Luo, Xue; Li, Mo; Zhang, Henan; Yan, Danli; Ji, Shuaiqi; Wu, Rina; Chen, Yongfu
Abstract: BACKGROUND: Lactobacillus plantarum, a common species of lactic acid bacteria, is used to improve the flavor of traditional fermented food. Under salt stress, different strains of L. plantarum can respond differently. In this work, proteomics and bioinformatics analysis of L. plantarum strains (ATCC14917, FS5‐5, and 208) grown under salt stress (240 g L −1 sodium chloride (NaCl)) were investigated based on the isobaric tags for relative and absolute quantitation method. RESULTS: Although 171 differentially expressed proteins (DEPs) were observed, only 44, 57, and 112 DEPs were identified in the strains ATCC14917, FS5‐5, and 208 respectively. There were 33, 191, and 179 specific DEPs in ATCC14917 versus FS5‐5, in 208 versus FS5‐5, and in strain 208 versus ATCC14917 in 240 g L −1 NaCl. These DEPs indicate that the three strains, from pickles, fermented soybean paste, and fermented milk, may have different salt stress responses. Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes analysis showed that most DEPs observed were involved in protein biosynthesis, nucleotide metabolism, and sugar metabolism. Twenty‐six significantly different DEPs that were possibly associated with salt response were selected and further analyzed for gene expression level and pattern by quantitative reverse transcription polymerase chain reaction. Pyruvate kinase and cysteine desulfurase had similar expression patterns in all three strains; glutamate decarboxylase expression was upregulated in FS5‐5 and significantly upregulated in strain 208; RNA polymerase subunit alpha was downregulated in FS5‐5 but upregulated in strain 208. CONCLUSIONS: These results also showed that the salt stress response of strain 208 may involve higher numbers of genes than the other strains. This research provides a theoretical basis for improvement of salt tolerance of L. plantarum in industrial production. © 2020 Society of Chemical Industry